Mountain ecosystems of India - Negi, S. S. (Dehradun Bishen Singh Mahendra Pal Singh, 2014)
This book provides a description of the mountain ecosystems of India, including that of the Himalayan range; Western and Eastern Ghats, Aravalli, Vindhyan, Satpura mountains and the hills of north-east India. It covers climate, soils, land use, flora, fauna, forests and grassland ecosystems; wet land ecosystems and protected areas. It is a handy book for the scientist, student, researcher, naturalist and the lay man.
Keywords: Mountain ecology - Himalaya Mountains; IFoS as an author; Indian Forest Service